Enhancing Localized, Occlusal Space by Relative Axial Tooth Movement in Patient with Dentinogenesis Imperfecta—A Case Report - Mohammad Abdullah Zayed Alqhtani (Journal of Pharmacy and Bioallied Sciences)
Dentinogenesis imperfecta (DI) is a hereditary disorder that affects dentin formation, leading to discolored, fragile teeth with increased susceptibility to wear and fracture. A 41-year-old woman presented with a family history of DI and significant tooth wear primarily affecting her maxillary anterior teeth due to parafunctional habits. She reported dissatisfaction with her smile, indicating that her front teeth were short and did not show when smiling. Examination revealed blue-gray teeth with craze lines characteristic of DI, receded pulp chambers, and evidence of significant tooth surface loss due to attrition. The patient had no significant medical history or allergies, with a regular history of dental attendance. The management plan involved restorative treatment using a staged approach. Initially, non-surgical debridement, management of caries, and the placement of provisional restorations using a fixed Dahl appliance were performed to create occlusal space. This was followed by definitive ceramic restorations to restore esthetics and function. The treatment successfully improved the patient’s smile and functional outcomes. This case highlights the importance of a comprehensive, phased treatment approach for managing DI, emphasizing the need for occlusal space creation, caries management, and esthetic restoration to improve patient satisfaction and dental health outcomes.